Association of Trabecular Bone Score (TBS) With Incident Clinical and Radiographic Vertebral Fractures Adjusted for Lumbar Spine BMD in Older Men: A Prospective Cohort Study. (7th April 2017) - Schousboe, John T; Vo, Tien N; Langsetmo, Lisa; Taylor, Brent C; Cawthon, Peggy M; Schwartz, Ann V; Bauer, Douglas C; Orwoll, Eric S; Lane, Nancy E; Barrett‐Connor, Elizabeth; Ensrud, Kristine E
ABSTRACT: The association of trabecular bone score (TBS) with incident clinical and radiographic vertebral fractures in older men is uncertain. TBS was estimated from baseline spine dual‐energy X‐ray absorptiometry (DXA) scans for 5831 older men (mean age 73.7 years) enrolled in the Osteoporotic Fractures in Men (MrOS) study. Cox proportional hazard models were used to determine the association of TBS (per 1 SD decrease) with incident clinical vertebral fractures. Logistic regression was used to determine the association between TBS (per 1 SD decrease) and incident radiographic vertebral fracture among the subset of 4309 men with baseline and follow‐up lateral spine radiographs (mean 4.6 years later). We also examined whether any associations varied by body mass index (BMI) category. TBS was associated with a 1.41‐fold (95% confidence interval [CI] 1.23 to 1.63) higher aged‐adjusted odds of incident radiographic fracture, and this relationship did not vary by BMI ( p value = 0.22 for interaction term). This association was no longer significant with further adjustment for lumbar spine bone mineral density (BMD; odds ratio [OR] = 1.11, 95% CI 0.94 to 1.30). In contrast, the age‐adjusted association of TBS with incident clinical vertebral fracture was stronger in men with lower BMI (≤ median value of 26.8 kg/m 2 ; hazard ratio [HR] = 2.28, 95% CI 1.82 to 2.87) than in men with higher BMI (> median; HR = 1.60, 95% CI 1.31 to 1.94; p value = 0.0002 for interaction term). With further adjustment for lumbar spine BMD, the association of TBS with incident clinical vertebral fracture was substantially attenuated in both groups (HR = 1.30 [95% CI 0.99 to 1.72] among men with lower BMI and 1.11 [95% CI 0.87 to 1.41] among men with higher BMI). In conclusion, TBS is not associated with incident clinical or radiographic vertebral fracture after consideration of age and lumbar spine BMD, with the possible exception of incident clinical vertebral fracture among men with lower BMI. © 2017 American Society for Bone and Mineral Research.